Aggression and Violence in Mental Health Inpatient Units: A Case Study at The Accra Psychiatric Hospital. - Adjei-Sarpong, A.A.H. (University of Ghana., 2019)
Background: The incidence of aggression and violence towards healthcare workers appear to be an everyday issue (Spencer et al, 2010). This is because, with patients who are mentally ill, there is always a cause for aggression and violence due to a combination of factors such as intense mental distress and personality, physical, environmental and behavior and attitudes of healthcare workers. The study sought to achieve three objectives at the Accra Psychiatric Hospital; to examine the prevalence of aggression and violence, assess the effect of aggression and violence on the output of inpatient health workers as well as assessed the hospital’s management’s response to aggression and violence. Method: the study adopted a quantitative approach. Purposive sampling method was used in selecting 100 health care workers. Similarly, the study reviewed hospital records on violence and aggression for the period 2012 to 2016. The dependent variable for the study was level of work output whiles violence and aggression were the independent variables. Stata 15.1 was used to process the data as well as descriptive and inferential statistics in the analysis. Results and Conclusion: the results of the study revealed that, cases of aggression and violence was prevalent especially in male patients than female patients. On the effects of aggression and violence on work output, inpatient health workers identified experience of being bitten, shouted at, kicked, hit and pushed by patients and these subsequently led to anxiety, depression and extra workload or duty after work. It was also revealed that, inpatient health workers who has been shouted at were likely to be productive than those who had ever been shouted at. This was the same case as inpatients that had never been experienced violence. They were more likely to be productive than those who experience violence. The hospital management’s response to aggression and violence by patients was through the use of medication, seclusion and negotiation. Given these points, it may be said that issues of aggression and violence towards inpatient health workers were inevitable in the Accra psychiatric hospital. The study recommended that, mental health institutions should employ more inpatient health workers to relief the over burden of already existing inpatient health workers ratio.
MA. Public Health
Keywords: Aggression and Violence; Mental Health; Inpatient; Accra Psychiatric Hospital; Health Care Workers